2014
DOI: 10.1164/rccm.201404-0670oc
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Anatomic Defect of the Cystic Fibrosis Airway

Abstract: Rationale: The mechanisms underlying cystic fibrosis (CF) lung disease pathogenesis are unknown.Objectives: To establish mechanisms linking anion transport with the functional microanatomy, we evaluated normal and CF piglet trachea as well as adult swine trachea in the presence of selective anion inhibitors.Methods: We investigated airway functional microanatomy using microoptical coherence tomography, a new imaging modality that concurrently quantifies multiple functional parameters of airway epithelium in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
169
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 136 publications
(187 citation statements)
references
References 55 publications
18
169
0
Order By: Relevance
“…The velocity of mucus transport in this sequence was also measured to be 71 ± 28 µm/s. These values were in accordance with previous results derived from ex vivo swine trachea [10,11,13]. Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The velocity of mucus transport in this sequence was also measured to be 71 ± 28 µm/s. These values were in accordance with previous results derived from ex vivo swine trachea [10,11,13]. Fig.…”
Section: Resultssupporting
confidence: 93%
“…More recently, we have utilized µOCT for in vitro imaging of the airway surface, including the cilia [10][11][12][13][14]. Cilia are microscopic organelles that line respiratory epithelia and beat repeatedly in a sweeping motion to clear mucus from the airways.…”
Section: Introductionmentioning
confidence: 99%
“…Although male rats of both genotypes grow larger than females of the same age, there was no detectable sex-related difference in histomorphometry. To assess the function of tracheal submucosal glands and the effect of their secretions on the airway surface at 1, 3, and 6 months of age, tracheae were imaged under μOCT as previously described (22,24,26,34) and the airway surface liquid (ASL) depth was measured before and after cholinergic stimulation with acetylcholine ( Figure 2A). Comparison of ASL depths of KO rats to those of their age-matched WT littermates showed that ASL depths were diminished in both basal and stimulated conditions, from weaning until at least 6 months of age (WT 1 month 22.9 ± 4.6 μm, 6 months 43.6 ± 12.5 μm vs. KO 1 month 6.9 ± 0.7 μm, 6 month 19.5 ± 4.8 μm; P < 0.05 at all ages, Figure 2, B and C).…”
Section: Resultsmentioning
confidence: 99%
“…In vivo studies of the CF mucus abnormality have been limited, as the CF mouse models do not accurately replicate the muco-obstructive lung disease characteristic of human patients with CF (17,18). While significant insights have arisen from the CF pig and ferret models (19)(20)(21)(22)(23)(24), particularly regarding mucus secretion and release at the onset of disease (13,25), these models are less amenable for longitudinal studies to characterize how CF pathogenesis ensues over time. These limitations have led us to develop a Cftr -/-rat (here referred to as the CFTR…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of this study is that loss of CFTR may influence the function of other cell types and structures, including submucosal glands (31,55), airway smooth muscle (56), cartilage (57,58), and myeloid-derived cells (59). Impairment of their function might also contribute to the pathogenesis of CF airway disease.…”
Section: As Hcomentioning
confidence: 99%